An assessment of knowledge level and training gap of the farmers regarding post-harvest losses of wheat in Punjab, Pakistan - Manzoor, Adeela; Tanvir, Farooq Tanwir; Akhtar, Saira; Shahbaz, Babar (Journal of Pure and Applied Agriculture, 2023)
The major objective of this study was to assess the training needs of farmers to reduce the post-harvest losses of wheat. For this purpose, face to face interviews were conducted to assess the training needs of farmers from four hundred (400) farmers selected on the basis of multi-stage sampling technique. Results of the study show that one-third (28.5%) of the respondents have 20 years and above farming experience